Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

United in anger: a history of ACT UP (United in Anger, Inc., 2012)
"A unique feature-length documentary that combines startling archival footage that puts the audience on the ground with the activists and the remarkably insightful interviews from the ACT UP Oral History Project to explore ACT UP (the AIDS Coalition to Unleash Power) from a grassroots perspective - how a small group of men and women of all races and classes, came together to change the world and save each other's lives."
Place: États-Unis
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; act up; amériques; approches et analyses; cinéma; communication; cours; discipline; documentaire; film; intersectionnalité; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; états-unis

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Section: 187, [4] pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis